Persuasive functions of photo galleries on information websites - Kampka, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article presents a rhetorical analysis of online galleries. The author argues that the selection of photographs presented in a gallery serves the purpose of fulfilling a persuasive goal. That is proved by, as indicated in the analysis, the verbal and visual markers of coherence, and the narrativeness visible at the level of individual photographs, groups of photographs, and the entire gallery.